The Comparison between Visual Learners and Kinesthetic Learners in Reading Comprehension at the Eleventh Grade Students of SMA Negeri 2 Pamekasan - Dewi, Sakinah Aprilia; Hasanah, Henny Uswatun (PANYONARA: Journal of English Education, 2020)
Comprehending English text is still one of the focuses on the English teaching-learning process in Indonesia. However, students’ ability to comprehend English reading text is various. Some theories mentioned that reading comprehension of the students is influenced by students' learning styles. This research is to compare reading comprehension between visual and kinesthetic learners at the eleventh-grade students of SMA Negeri 2 Pamekasan. This study used a quantitative approach with a causal-comparative design. The population of this research was 320 eleventh grade students with the sample was taken were 48 students or 15% of the population. The data were collected using Sensory Learning Style Questionnaire to divide students based on their learning style and Reading Comprehension test to measure students' reading comprehension. The obtained data were analyzed by using the independent t-test to compare the significant difference between visual and kinesthetic learners. The statistical analysis was computed using SPSS 16. The result proved that obtained t-value was lower than t-table with significant 5% and 1% (1.084 < 2.06 and 1.084 < 2.79) which showed that the achievement of reading comprehension of visual students was same as kinesthetic learners at the eleventh-grade students of SMA Negeri 2 Pamekasan